A comparative study of the Au-catalyzed cyclization of hydroxy-substituted allylic alcohols and ethers - Berenger Biannic; Thomas Ghebreghiorgis; Aaron Aponick (Beilstein Journal of Organic Chemistry, 2011)
The Au(I)-catalyzed cyclization of hydroxyallylic ethers to form tetrahydropyrans is reported. Employing (acetonitrile)[(o-biphenyl)di-tert-butylphosphine]gold(I) hexafluoroantimonate, the cyclization reactions were complete within minutes to hours, depending on the substrate. The reaction progress was monitored by GC, and comparisons between substrates demonstrate that reactions of allylic alcohols are faster than the corresponding ethers. Additionally, it is reported that Reaxa QuadraPureTM MPA is an efficient scavenging reagent that halts the reaction progress.